أهمية استخدام نموذج القيمة الاقتصادية المضافة كمؤشر لتقييم أداء الشركات المساهمة من وجهة نظر المساهمين، دراسة تطبيقية. - أسعد, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتناول الدراسة مقياس "القيمة الاقتصادية المضافة" كمؤشر لتقييم أداء الشركات، وأهميته للمساهمين لاتخاذ قراراتهم الاستثمارية. عرضت الدراسة المقاييس التقليدية لتقييم الأداء المستندة إلى الربح المحاسبي، ومن ثم مقارنتها مع مقياس القيمة المضافة بوصفه مقياسا يستند إلى الربح الاقتصادي. أُجريت دراسة تطبيقية على بيانات شركة مساهمة سورية لسلسلة زمنية من خمس سنوات، بغرض احتساب القيمة الاقتصادية المضافة ومقاييس العائد، ومقارنتها مع تحليل المؤشرات المستخلصة منها. وقد خلصت الدراسة إلى وجود تباين بين منفعة المعلومات المستمدة من تلك المقاييس من منظور تعظيم ثروة المساهمين، وأوصت بضرورة قياس القيمة الاقتصادية المضافة التي تخلقها الشركات والإفصاح عنها ضمن التقارير المالية لتلك الشركات. The study deals with Economic Value Added Model (EVAM) as a metric to evaluate the performance of companies, and its importance to the shareholders to make their investment decisions. It applies the traditional metrics used in evaluation of performance who based on accounting profit, and compare it with the economic value added as a metrics based on economic profit. The study was conducted on data of Syrian corporate company for a period of five years, to calculate the metrics "economic value added" and "return" metrics, and then make a comparison and analysis of indicators derived from them. The study concluded that there is a difference between the benefit of information derived from those metrics in the perspective of maximizing shareholder wealth. It recommended the need to measure the economic value added created by companies and disclosing it in the financial reports of companies.